Pengaruh Daya Tarik Wisata Dan Electronic Word Of Mouth Terhadap Minat Kunjungan Wisatawan Pasca Revitalisasi Di Situ Gede Bogor - Rahmavati, Amalia; Pujiastuti, Sri (Jurnal Ilmiah Pariwisata Kesatuan, 2025)
This study explores the potential and impact of the revitalization of Situ Gede as a tourist destination in Bogor City. Revitalization involves infrastructure development, increased accessibility, and conservation efforts, increasing its attractiveness. However, development has not been optimal. This study aims to assess the influence of tourist attraction and Electronic Word of Mouth on tourist interest after revitalization. This study uses a quantitative approach with a data collection method using a questionnaire to 100 respondents who are selected according to the criteria by the purposive sampling method. The data test method used is SmartPLS version 4. The results of this study show that: 1) Tourism Attraction has a positive and significant effect on Tourist Visiting Interest. 2) Electronic Word of Mouth has a positive and significant effect on Tourist Interest in Visitation. 3) Tourist Attraction and Electronic Word of Mouth simultaneously have a positive effect on Tourist Visitor Interest. The results in this study show that Electronic Word of Mouth has a greater influence on the interest of tourist visits. Keyword: Tourist Attraction, Electronic Word of Mouth, Tourist Visit Interest